AN ANALYSIS OF THE FACTORS AFFECTING STUDENTS’ ENGLISH SPEAKING PROFICIENCY - Muhammad Muklas; Revina Yuliana; Evi Nurkhasanah; Lilis Nur Fahriza; Sefti Zhintia Yulianda (Wiralodra English Journal, 2024)
English includes common skills such as listening, reading, speaking, and writing. Many students focus on speaking skills and complain that English is a difficult language to use or pronounce. This is not easy when we are born with students whose everyday language is not English, which can make it difficult for these students. There are quite a few students today whose ability to speak English is still not good. Of course, there must be a solution to the problem. Therefore, this research aimed to find out what factors affect students English speaking proficiency. This research uses qualitative methods. Among them, in this research the process of identifying, classifying, and analyzing data according to the data analysis procedures in this study. There were 24 students sampled in this research. The results of this research are; the factors affecting students English speaking proficiency. These two factors are affective factors (risk-taking and motivation) and linguistic factors (grammar and vocabulary); (2) the oral performance test results of 24 students currently explain that their oral performance results are at the 5th-grade level or higher with a total average of 5.0.